2016
DOI: 10.1007/s00737-016-0645-1
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress and hemodynamics in pregnancy: a systematic review

Abstract: Purpose: Maternal prenatal stress is associated with preterm birth, intrauterine growth restriction, and developmental delay. However, the impact of prenatal stress on hemodynamics during pregnancy remains unclear. This systematic review was conducted in order to assess the quality of the evidence available to date regarding the relationship between prenatal stress and maternal-fetal hemodynamics. Methods:The PubMed/Medline, EMBASE, PsycINFO, Maternity and Infant Care, Trip, Cochrane Library, and CINAHL databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 112 publications
(161 reference statements)
0
18
0
Order By: Relevance
“…Moreover, an association between prenatal stress and changes in Doppler waveform parameters remain inconclusive due to the methodological limitations of available studies (27). Further investigations are necessary to clarify the effect of vasopressors on uteroplacental blood flow and fetal well-being in these high-risk settings.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an association between prenatal stress and changes in Doppler waveform parameters remain inconclusive due to the methodological limitations of available studies (27). Further investigations are necessary to clarify the effect of vasopressors on uteroplacental blood flow and fetal well-being in these high-risk settings.…”
Section: Resultsmentioning
confidence: 99%
“…The overall sample size and sample sizes at each time point in the current study are also relatively large within the context of the available literature on prenatal stress and fetoplacental Doppler velocimetry. 12 Moreover, because this was an SGA sample, it was possible to examine associations between maternal stress and abnormal Doppler findings, while most studies to date have reported statistically but not clinically significant associations with continuous outcomes. None of the 12 studies reporting associations between prenatal stress and Doppler ultrasound also reported neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 7–11 Although evidence links pregnancy-specific stress and fetal and infant outcomes, potential mechanistic pathways such as fetoplacental haemodynamics remain relatively unexplored. A recent systematic review reported 12 studies of prenatal stress and haemodynamics in pregnancy as measured by Doppler ultrasound; 12 only three measured pregnancy-specific stress. 13–15 There is therefore an evidence gap regarding potential associations between pregnancy-specific stress and fetoplacental haemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] While precise mechanisms remain unknown, it has been postulated that stress influences hormonal pathways leading to changes in host immune response, thereby affecting the cervicovaginal ecosystem. [27][28][29][30] These findings raise questions as to whether stress may promote colonization of the cervicovaginal space with a nonoptimal microbiota in pregnancy.…”
mentioning
confidence: 99%